Come on in, the water's lovely. - Wilson, Rob (Architects' Journal, 2025)
The article focuses on the Dock Shed, a newly completed building within the Canada Water Masterplan in Rotherhithe, London, which integrates workspace and a public leisure centre. Designed by Allies and Morrison, the building features a distinctive sawtooth steel roof and accommodates various uses, including commercial office space and a council-run leisure centre with extensive facilities. The project emphasizes sustainability, utilizing low-carbon materials and innovative design to reduce embodied carbon emissions significantly. The Dock Shed is part of a larger development plan that aims to revitalize the area, providing a mix of residential, retail, and cultural spaces while respecting the site's industrial heritage.